If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + -1x) = -18 (2 * 3 + -1x * 3) = -18 (6 + -3x) = -18 Solving 6 + -3x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -3x = -18 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = -18 + -6 -3x = -18 + -6 Combine like terms: -18 + -6 = -24 -3x = -24 Divide each side by '-3'. x = 8 Simplifying x = 8
| 5-x=-7 | | 2x+3y=7y-13 | | Y-3y=8-6 | | (4y+7)-(6+3y)=6 | | -(5x+5)-(8x-7)=6-(4x+1) | | .50(16-x)=-12(x+7) | | -(b-7)-9(b-3)=8b-4b | | 3p-6p= | | 3(d+12)=-17p-5 | | -5y-y^2+4y^2-6y= | | Y+3y=8-2 | | (4+3i)(3i-4)= | | 0=(25x^2)/(x-2)+9-(2x)/(x-2) | | 7/5(-36/5r+1/4)+17/4=2077/150-5/6r | | 20+g=14 | | 6-6n+3n=31-97 | | .05x-.6=5.3 | | 15x-6x+18=7 | | 2/3x+1=6-(1/3x-3) | | 5b-6=14 | | 9n+4.3=43.9 | | -16=8(x+13) | | Y=-343 | | 2x^2-x+x^2-3x= | | m^2=1190 | | 13n-10n=5+7 | | y=x(3x+2) | | 786+(-84)= | | Y=log(x-5) | | -16-2n-5+8n=65 | | F(x)=-343 | | 24-6r=6r(4-r) |